Analysis of children with familial short stature: who should be indicated for genetic testing? - Plachy, Lukas; Petruzelkova, Lenka; Dusatkova, Petra; Maratova, Klara; Zemkova, Dana; Elblova, Lenka; Neuman, Vit; Kolouskova, Stanislava; Obermannova, Barbora; Snajderova, Marta; Sumnik, Zdenek; Lebl, Jan; et al. (Endocrine connections, 2023)
Familial short stature (FSS) describes vertically transmitted growth disorders. Traditionally, polygenic inheritance is presumed, but monogenic inheritance seems to occur more frequently than expected. Clinical predictors of monogenic FSS have not been elucidated. The aim of the study was to identify the monogenic etiology and its clinical predictors in FSS children. Of 747 patients treated with growth hormone (GH) in our center, 95 with FSS met the inclusion criteria (pretreatment height ≤-2 SD in child and his/her shorter parent); secondary short stature and Turner/Prader-Willi syndrome were excluded criteria. Genetic etiology was known in 11/95 children before the study, remaining 84 were examined by next-generation sequencing. The results were evaluated by American College of Medical Genetics and Genomics (ACMG) guidelines. Nonparametric tests evaluated differences between monogenic and non-monogenic FSS, an ROC curve estimated quantitative cutoffs for the predictors. Monogenic FSS was confirmed in 36/95 (38%) children. Of these, 29 (81%) carried a causative genetic variant affecting the growth plate, 4 (11%) a variant affecting GH-insulin-like growth factor 1 (IGF1) axis and 3 (8%) a variant in miscellaneous genes. Lower shorter parent's height (P = 0.015) and less delayed bone age (BA) before GH treatment (P = 0.026) predicted monogenic FSS. In children with BA delayed less than 0.4 years and with shorter parent's heights ≤-2.4 SD, monogenic FSS was revealed in 13/16 (81%) cases. To conclude, in FSS children treated with GH, a monogenic etiology is frequent, and gene variants affecting the growth plate are the most common. Shorter parent's height and BA are clinical predictors of monogenic FSS.
Keywords: next-generation sequencing; GH treatment; predictors of monogenic short stature; growth plate disorders; familial short stature